Pemanfaatan Jalur Lintas Selatan Tulungagung Terhadap Potensi Pariwisata Kecamatan Besuki - Elha Fawwa DM; Aurelia Azzahra; Irma Yunita; Lailatut Habibah (Universitas 45 Surabaya, 2024)
The use of the Tulungagung Southern Cross Route for the tourism potential of Besuki District is research that aims to analyze the impact of new road infrastructure on the development of the tourism sector in the region. The Southern Cross Route (JLS), which connects several potential tourist destinations in Besuki District, is expected to increase accessibility and attract more tourists. This research uses a qualitative method with a descriptive approach to evaluate changes that occurred before and after the construction of the JLS. Data was obtained through direct observation, interviews with local stakeholders, and analysis of related documents. The research results show that JLS has made a positive contribution in increasing the number of tourist visits, developing tourism facilities, and empowering the local community's economy. However, research also identifies several challenges such as the need for improved supporting facilities and more effective promotions. In conclusion, the use of JLS provides great opportunities for tourism development in Besuki District, but requires a sustainable strategy to maximize its potential.